Collaboration: Tens' Sticks for Sharing One's Burden - Yunus, Emran Bin (Journal of Chittagong Medical College Teachers' Association, 2010)
DOI: 10.3329/jcmcta.v20i1.4925 Journal of Chittagong Medical College Teachers' Association 2009: 20(1):1